Search Engine Optimization for Dummies - Kent, Peter (Wiley Publishing, 2011)
This book demystifies the world of search engines. You find out what you need to do to give your site the best possible chance to rank well in the search engines. In this book, I show you how to Make sure that you’re using the right keywords in your Web pages. Create pages that search engines can read and will index in the way you want them to. Avoid techniques that search engines hate — things that can get your Web site penalized (knocked down low in search engine rankings). Build pages that give your site greater visibility in search engines. Get search engines and directories to include your site in their indexes and lists.Encourage other Web sites to link to yours. Keep track of how well your site is doing. Use pay-per-click advertising and shopping directories. And plenty more!